FUNGSI SITUS TUTARI, IRIAN JAYA : TINJAUAN ASPEK SIMBOLIK - Sunarningsih (BRIN, 2001)
Basically, the Bukit Tutari Site is a worship / ceremony site. The worship is related to the characters they consider to have the life force, namely the head of war and the people who died because of the war. By means of these people, it is hoped that they will be able to reach the world of their ancestors that they desire. A place where there is only eternal happiness. As objects of worship, they erected menhir, lined stones, circular stones, and rock paintings.